A Model Study of Splash in a Peirce-Smith Converter - Yasumasa Hattori; Kimiaki Utsunomiya; Yoshiaki Mori; Toyokazu Okubo (The Minerals, Metals and Materials Society, 2000)
"The effect of various operating conditions on splashing behavior in a Peirce-Smith converter has been investigated with a 1/5.7 scale cold model. Dynamic similarity between the model and a commercial converter was attained by setting the modified Froude number in the model experiments in· the range for normal converter operation. It is known that for a given modified Froude number the dimensionless penetration length of gas into the liquid phase increases as the liquid density decreases. Moreover, penetration· length has a large effect on splashing behavior. Therefore, a heavy liquid, a mixture of water and lead concentrate was used as the liquid phase. It was concluded that the amount of splash dramatically decreases with a reduction in the buoyancy energy per, unit liquid mass and an increase in the horizontal distance between the tuyere tip and the edge of the mouth.IntroductionSubmerged gas injection is widely used in practice in ferrous and nonferrous pyrometallurgical operations to achieve large gas-liquid contact areas and good agitation of liquid for rapid chemical reaction. The common application in ·nonferrous industry is the Peirce-Smith converter with multi-tuyere for copper and nickel matte converting. This process has been used for over 100 years because of its effectiveness in mixing of the molten bath, as well as its merits of the engineering simplicity. However, the mechanisms which · determine the blowing performance is poorly understood, and the design and operating conditions of the Peirce-Smith converter varies widely from plant to plant, such as by diameter, length, mouth angle, tuyere position and level of molten matte. Smelters have continuously made an effort to increase converter productivity, implying maximum tuyere blowing rate. Above a certain critical blowing rate, splash of molten matte from the converter mouth becomes unacceptable because of dangerous ejection and accretion buildup around the converter mouth, which results in interference with effective hood sealing. In fact, a 1993 converter survey[!] reported that splash was a major limiting factor for blowing rate and 54% of responding plants from around the world regard it as a limiting condition[2]. In order to increase tuyere blowing rate a study of the effect of various operating conditions on splashing behavior is expected."